GREEN OPEN SPACE PERFORMANCE AS URBAN RECREASTION RESOURCES IN PEKANBARU - Wahyu Hidayat (TATALOKA, 2011)
Urban green open space has significant benefits for the condition of urban living and its community. The availability of accessible and attractive green spaces for recreation activities is an integral part of urban quality of life. This research aims to assess the effectiveness of green open space provision as recreation resource for urban citizens in Pekanbaru, Indonesia. This study presents the assessment of two ele-ments which are equity and efficiency. These two elements are analyzed based on numerous independent variables such as number of the facil-ity, distance to house, accessibility and public transportation availability for equity assessment and frequency of usage, attractiveness of fa-cilities and safety level for efficiency assessment. The assessment of those variables is applied in three different subdistricts in Pekanbaru which are City Center, Sail and Tampan that represent different density categories. To achieve the objectives of this study, the method used to con-duct the study is field survey by questionnaire and interview. Stratified random sampling was the method used in data collection through the distribution of questionnaire, and the tool used to analyse data is through the Statistical Package for Social Science (SPSS). The data was analysed using descriptive statistics to obtain frequency distributions, percentage and the level of equity and efficiency. Several types of test in SPSS data analysis are included to attain some significant information in the study such as Chi-Square test of independence and analysis of Correlation. The findings indicate that a majority of respondents were not satisfied with the distribution of green open space. This study also identified that the quality of green open space facilities was perceived by residents as at moderate level. This survey results indicate that there is significant relationship between subdistricts of respondents and the satisfaction level of green open space distribution. The study could be useful for decision makers, professionals and researchers related to urban and recreation planning to achieve a better quality of life.